Code-Switching in French and Francophone Studies Classrooms in a Ghanaian Public University: Exploring Perceptions and Motivations - Abban, Albert; Mensah, Dorah; ResCue, Elvis (Global Journal of Educational Studies, 2024)
Code-switching in language classrooms is a contentious topic of debate, with some experts advocating for the monolingual use of the target language as the medium of instruction, while others support a bilingual approach such as code-switching and translanguaging. This paper examines the motivations for code-switching and the perceptions of both lecturers and students on bilingual practices in French and Francophone Studies classrooms. The study adopted a mixed research design, gathering data through interviews, classroom observation and an online questionnaire using a Google Form interface. The questionnaires were distributed to students via their WhatsApp platforms. A total of 120 French students filled out the questionnaires and 5 lecturers were selected for the interview session. The findings revealed that lecturers employ code-switching to address the linguistic needs of both Anglophone and Francophone students in the classrooms. The reasons for code-switching included students’ limited language background, low proficiency in the French language, inadequate teaching materials, situational factors, and the relevance of other languages in French classrooms. Overall, the majority of the lecturers and students expressed a positive perspective towards code-switching use in the classroom stating that such code choices facilitate the understanding of concepts and contribute to interactive classroom experiences. There was, however, the caution against its pervasive use as it hinders the ability to learn and speak the French language.